Augmented reality on mobile devices: navigation and interaction models and information visualization models - Nascimento, Ricardo (2013)
This paper describes a set of navigation and interaction and information visualization models, whose conceptualization and development is a research work of the Master in Multimedia Communications held in an enterprise context (PT Inovação), taking into account augmented reality scenarios in tablet devices with a large set of possible applications. Starting with a brief introduction on theoretical issues underlying the research, the paper advances with a description and illustration of each model. It is also discussed a case-study, where a prototype has been developed, operationalizing some of the navigation and interaction models conceptualized, as well the stage of testing and validation of the prototype and used modals. The document ends with some concluding remarks.?